Pengaruh Gaya Kepemimpinan Transaksional dan Transformasional terhadap Kinerja Karyawan dengan Komitmen Organisasi - Muhammad Zulkarnain; Rizal P Lubis; Fauza Pratama (Universitas Harapan Medan, 2022)
This study aims to determine the effect of transactional and transformational leadership styles on the performance of employees of PT. Build Mitra Abadi Medan either partially or simultaneously. To find out whether organizational commitment moderates the effect of transactional leadership styles and transformational leadership styles on employee performance at PT. Build Mitra Abadi Medan. The population in this study amounted to 163 people and using the Slovin formula obtained a sample of 116 people. The analysis technique used is multiple linear regression and MRA residual techniques. The results showed that the transactional leadership style had a significant effect on the performance of the employees of PT. Build Mitra Abadi Medan. Transformational leadership style affects employee performance at PT. Build Mitra Abadi Medan. Organizational commitment has been shown to be significant in moderating transactional leadership styles on employee performance and organizational commitment has been proven significant in moderating transformational leadership styles on employee performance.